Countering Journalist Curse in A Bourdieusian Perspective: Metajournalistic Discourse on Doxing in Remotivi Indonesia - Krisdinanto, Nanang (Universitas Ahmad Dahlan, 2024)
This research explores the phenomenon of doxing as a digital form of attack against journalists, reflecting a shift from physical threats to digital harassment facilitated by the accessibility of digital media. Utilizing a metajournalistic discourse approach, this study examines how Indonesian journalists perceive and respond to the pressures of doxing within the framework of their professional practices and identities. By analyzing metajournalistic discourse documents from the Remotivi website, this research positions journalists as both victims and defenders within their field, facing pressures from both the political and economic spheres. Pierre Bourdieu’s theoretical constructs of the journalistic field, capital, and habitus are employed to interpret the responses of journalists to these digital threats. The findings indicate that doxing represents a significant external influence, perpetuating a high degree of heteronomy within the journalistic field. However, there also exists a discursive resistance among journalists, characterized by efforts to define and uphold a journalistic identity aligned with autonomy and ethical norms. This study highlights the need for greater cybersecurity awareness and protections for journalists, emphasizing the importance of maintaining journalistic integrity in the face of evolving digital threats.